Pengaruh leverage dan profitabilitas terhadap peringkat obligasi - Pramesti, Dyah Sisca Putri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The goal of this study is to ascertain how partial leverage has an impact on bond ratings, between 2016- 2019, the influence of profitability on bond ratings, as well as the simultaneous effect of leverage and profitability on bond ratings in the property, real estate, and construction industries listed on the Indonesian stock exchange. Leverage is measured using debt-to-equity ratio proxies, and profitability is measured using return on assets as an independent variable, while bond ratings are measured using ratings from the rating agency PT. PEFINDO as a dependent variable. All companies in the property, real estate, and construction industries that were publicly traded on the Indonesian Stock Exchange between 2016 and 2019 are included in this study's population. The sample is comprised of firms that issued bonds between 2016 and 2019, and the sampling approach is non-probability sampling with purposive sampling, yielding a total sample of ten companies or forty financial statements. The data analysis approach employed is linear regression with a 5% significance threshold, utilizing the SPSS 26 and Eviews 10 software packages. According to the conclusions of this study, leverage has a limited impact on bond ratings, profitability has a limited impact on bond ratings, and both leverage and profitability have an impact on bond ratings. simultaneously.